When the long road is the shortcut: a comparison between two coding methods for content-based lie-detection tools. - Nahari, Galit (Psychology, Crime & Law, 2016)
When using a content-based lie detection tool, a decision regarding veracity is made by evaluating the presence of specific content criteria within the interviewee’s account. This evaluation can be achieved either by counting the frequency of occurrence of the criteria (frequency counts; FC) or by using a scale to rate the intensity at which they appear in the entire text (scale rates; SR). In the current study, we compared these two coding methods with respect to their accuracy in determining veracity, and their intercoder and test–retest reliabilities. Fourteen coders coded the presence of perceptual and contextual details in true and false statements, each used the FC method for one set of 30 statements and the SR method for another set of 30 statements. One month later, eight of the coders recoded 28 statements. Results showed a significant advantage for the FC method over the SR method. While the coders perceived the SR method as less time-consuming than the FC method, accuracy level as well as intercoder and test–retest reliabilities were higher for the FC than for the SR method. These findings suggest that when using a content-based lie detection tool, FC coding should be preferred over SR coding.